Geophysics in Mining and Environmental Protection - Idziak, Adam F.; Dubiel, Ryszard; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
This book contains contributions to the 32nd Polish-Czech-Slovak Symposium on Mining and Environmental Geophysics held in May 2009 in Piechowice (Poland). The papers are related to various aspects of geophysical science such as induced seismicity, engineering seismology, environmental geophysics and geophysics in geology.
Evaluation of Seismic Effects Generated by Mining Induced Seismic Events in Stonava Area -- Moment Tensor Solution and Physical Parameters of Selected Recent Seismic Events at Rudna Copper Mine.- Seismic Loading of Medieval Jeroným Mine during West Bohemia Swarm in 2008 -- Spin and Twist Wave Packs in the Seismic Field: A Case of Mining Events -- An Analysis of Amplification Effects at Selected Polish Seismic Stations.- Investigation of the Medieval Jeroným Mine Stability: Present Results from a Disturbed Measurement Network -- Seismic and Geodetic Observations of Subsidence Trough Development over a Longwall Face in a Coal Bed under Extraction -- Suggestion of Complex Monitoring of Undermined Territory.-  Identification of Geotechnical Conditions in Areas of Former Shallow Mining Activity Using Geoelectrical Methods -- The Use of Seismic Methods to Determine Potential Directions of Underground Water Flow in Fractured Rock Mass -- Assessment of Fracture Properties from P-wave Velocity Distribution -- Electrical Resistivity Imaging Method in Investigating Post-Glacial Geomorphological Forms -- Frictional Metamorphism of Coal in the Upper Silesia Coal Basin, Southern Poland Suggestion of Complex Monitoring of Undermined Territory.-  Identification of Geotechnical Conditions in Areas of Former Shallow Mining Activity Using Geoelectrical Methods -- The Use of Seismic Methods to Determine Potential Directions of Underground Water Flow in Fractured Rock Mass -- Assessment of Fracture Properties from P-wave Velocity Distribution -- Electrical Resistivity Imaging Method in Investigating Post-Glacial Geomorphological Forms -- Frictional Metamorphism of Coal in the Upper Silesia Coal Basin, Southern Poland Frictional Metamorphism of Coal in the Upper Silesia Coal Basin, Southern Poland.
Keywords: Geophysics; Pollution prevention; Geophysics/Geodesy.; Industrial Pollution Prevention; Geophysics and Environmental Physics